ChemInform Abstract: Synthetic Entries to and Biological Activity of Pyrrolopyrimidines. Issue 10 (February 2016) - De Coen, Laurens M.; Heugebaert, Thomas S. A.; Garcia, Daniel; Stevens, Christian V.
Abstract: Review: recent literature (2000‐2015) on the synthesis and pharmaceutical properties opyrrolopyrimidines; 183 refs.